2001
DOI: 10.1161/hh0701.089955
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species and Death

Abstract: R eactive oxygen species (ROS) (eg, superoxide, peroxide, and hydroxyl radicals) and reactive nitrogen species (eg, peroxynitrite) are generated in both atherogenesis and advanced atherosclerosis, 1 particularly by macrophages. 2 ROS have many actions, including oxidative modification of LDL and oxidative damage of DNA. Oxidative Modification of LDLAlthough LDL is essential to deliver cholesterol to tissues, increased LDL cholesterol is associated with increased risk of cardiovascular disease. Oxidative modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…However, few studies explored the effects that diet has on DNA damage during the postprandial state, or the effect of CoQ supplements in humans. Previous evidence showed that DNA damage plays a crucial role in the mechanisms of atherosclerosis (Bennett 2001), as well as other diseases related to aging. In the same line, studies carried out on rats fed with diets rich in polyunsaturated fatty acids demonstrated that CoQ supplements have a protective effect against oxidative damage (Thomas et al 1996;Santos-Gonzalez et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies explored the effects that diet has on DNA damage during the postprandial state, or the effect of CoQ supplements in humans. Previous evidence showed that DNA damage plays a crucial role in the mechanisms of atherosclerosis (Bennett 2001), as well as other diseases related to aging. In the same line, studies carried out on rats fed with diets rich in polyunsaturated fatty acids demonstrated that CoQ supplements have a protective effect against oxidative damage (Thomas et al 1996;Santos-Gonzalez et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…6 A major feature of atherosclerosis includes increased levels of reactive nitrosative species (RNS) and reactive oxygen species (ROS) associated with damage to cell membranes and DNA. 7,8 It is not surprising therefore that PARP-1 inhibition was also shown to limit endothelial dysfunction and atherosclerosis in the ApoE Ϫ/Ϫ mouse. 6,9 High levels of ROS and RNS, such as occur in ischemia-reperfusion injury, inflammation, and diabetes mellitus, induce DNA single-strand breaks and activate poly-ADP ribose polymerase-1 (PARP-1).…”
mentioning
confidence: 99%
“…There is also evidence for ROS to cause oxidative DNA damage in endothelium (11,12), which contributes to the pathogenesis of atherosclerosis and to instability of plaques (13)(14)(15). In patients with cardiovascular disease, the levels of oxLDL and circulating 8-hydroxy-2Ј-deoxyguanosine (8-OHdG) DNA-adducts correlate well (16).…”
mentioning
confidence: 99%